About Translation Problems of Epic Texts - Vasilyeva, Sargylana Prokopievna (Journal of History Culture and Art Research, 2018)
For a qualitative translation of text it is necessary to preserve its style, style of the original. In translation practice, a whole arsenal of methods and techniques is used to select an adequate verbal equivalent in the target language. But the issues of style in the translation of epic texts in the communicative and activity aspect have not yet been considered. To understand the valuable information and interpretation of the text it is important to be able to distinguish and use existing stylistic structures and forms, in particular, compositional-vocal and architectonical. When analyzing the texts of olonkho, we rely on the linguistic concept of translation developed by prof. M.P. Brandes. Accordingly, genres and style are forms that determine the perception of meaning. This article studies compositional-vocal and architectonical forms of epic texts. The article implements linguistic analysis, including the method of direct observation, relative and comparative methods. The analysis of fragments of the olonkho translation allowed us to draw the following conclusions: 1. The ascertaining messages are prevalent. The secondary information is dominant in them, since the temporal and logical sequences are blurred by the enumerations that give to message an additional picture. Thus, in such messages, notional and semantic structures merge. 2. The nominative descriptions dominate, where the main semantic load carries the names - adjectives and nouns.